2017
DOI: 10.1148/radiol.2016160644
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Manifestation of Ormond Disease: The “Mistletoe Sign”

Abstract: A 69-year-old woman presented with symptoms of presumed cardiac involvement of idiopathic retroperitoneal fibrosis, otherwise known as Ormond disease. Distinct pericoronary tissue proliferations were depicted at cardiac magnetic resonance (MR) imaging and coronary computed tomographic (CT) angiography. On images, the coronary manifestation was termed the "mistletoe sign." The presence of the mistletoe sign on cardiac MR and coronary CT angiographic images is probably rare, but it might be a characteristic mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…CT angiography is observed the soft-tissue masses around the proximal segments of the left anterior descending (LAD) and right coronary artery (RCA). The presence "mistletoe sign" in CT angiography is an indicator of IgG4-RD associated coronary artery disease [70]. Mistletoe is a plant attached to the branches of a tree, similar to the perivascular soft, tissue attached to the coronary tree.…”
Section: Igg4-related Aortitis/periaortitismentioning
confidence: 99%
“…CT angiography is observed the soft-tissue masses around the proximal segments of the left anterior descending (LAD) and right coronary artery (RCA). The presence "mistletoe sign" in CT angiography is an indicator of IgG4-RD associated coronary artery disease [70]. Mistletoe is a plant attached to the branches of a tree, similar to the perivascular soft, tissue attached to the coronary tree.…”
Section: Igg4-related Aortitis/periaortitismentioning
confidence: 99%
“…Because IgG4-associated coronary inflammation occurs in the adventitia, it can result in inflammatory pseudotumor, perivascular fibrosclerotic thickening, luminal stenosis, and aneurysmal dilatation. The typical mistletoe sign in coronary computed tomographic angiography is indicative of the diagnosis of IgG4-associated coronary artery disease, as this case shows. Positron emission tomography and computed tomography are also useful in evaluation and follow-up of IgG4-related disease with coronary artery involvement; these can show hypermetabolic coronary artery masses and identify alternative biopsy sites …”
Section: Discussionmentioning
confidence: 59%
“…MU et al 1 and Horvat et al 2 described patients in whom IRPF manifestation was coronary arterial involvement and retroperitoneal mass. Yamakaw et al 3 demonstrated a case of retroperitoneal mass remission in a patient with IgG4-related RPF.…”
Section: Discussionmentioning
confidence: 99%